Estimation of fractures orientation from qP reflectivity using multiazimuthal AVO analysis - GOMES, Ellen de Nazaré Souza (2013)
We investigate the estimation of fractures orientation, strike and dip, through multiazimuthal AVO analysis of qP and its converted waves qS1 e qS2. We assume weak impedance contrast, weak anisotropy and that the fractured medium behaves as an effective transversally isotropic (TI) medium. Under these assumptions, the estimation of fractures orientation is reduced to the estimation of the orientation of an axis of symmetry from qP reflectivity data. Linearized approximations of qP reflectivity are used for inversion.